2011
DOI: 10.1021/nn102159g
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Targeting Dendritic Cell Surface Molecules Effectively Block T Cell Conjugation and Shift Response

Abstract: Dendritic cells (DCs) are potent professional antigen presenting cells (APC) that activate naïve T cells. Interaction of ICAM-1 and LFA-1 molecules on each cell is required for T cell conjugation to DCs which leads to naïve CD4+ T cell activation and proliferation. Nanoparticles capable of blocking LFA-1/ICAM-1 interaction were studied as inhibitors of T cell conjugation to DCs. Primary DCs were primed with ovalbumin, then treated with a peptide that binds ICAM-1 (LABL), a peptide that binds LFA-1 (cIBR) or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The shear associated with these processing conditions requires intensification to create increasingly smaller particle sizes, often damaging plasmid DNA to linear or fragmented forms [35]. In this study, we utilized a solvent diffusion technique that reduced shear and improved retention of DNA structure [3638]. Phenol/chloroform extraction assay revealed that PSMA aptamers were successfully conjugated onto the surface of the PLGA NPs (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shear associated with these processing conditions requires intensification to create increasingly smaller particle sizes, often damaging plasmid DNA to linear or fragmented forms [35]. In this study, we utilized a solvent diffusion technique that reduced shear and improved retention of DNA structure [3638]. Phenol/chloroform extraction assay revealed that PSMA aptamers were successfully conjugated onto the surface of the PLGA NPs (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work illustrated the advantages of monodisperse particles in controlling the release kinetics of drugs from the polymer matrix [3638]. Our recent studies also indicated that particle size can be optimized for different delivery purposes and plasmid DNA constructs can be encapsulated without any damage [43].…”
Section: Discussionmentioning
confidence: 99%
“…LABL is a peptide that inhibits the binding of intracellular cell-adhesion molecule-1 (ICAM-1) [32]. This peptide was also shown to interfere with immune cell adhesion in immortalized and primary cell culture models [33-35]. Coincident delivery of antigen and LABL, therefore, may inhibit the inflammatory immune response and provide ‘antigen-specific’ therapy for treating autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of co-cultures of DCs with T cells showed that nanoparticles targeting ICAM-1 or LFA-1 were significantly better inhibitors of synapse formation compared with similar concentrations of free ligands [164]. Furthermore, the targeted nanoparticles drammatically shifted the response of these cells as evidenced by a significant shift in cytokine expression profiles and T-cell proliferation.…”
Section: The Importance Of Multivalency: a Case Study Of Lfa-1 And Icam-1mentioning
confidence: 99%